'what doesn't kill you will make you stronger’ - F. Seling, Tenning (Universiti Teknologi MARA, Sarawak, 2004)
Kursus Tahap Kecekapan ( PTK ) is the latest evaluation method under 'Sistem Saraan Malaysia' to test one's professional proficiency. To adhere to the latest requirements, UiTM began conducting this course for in batches based on seniority late last year. Held over a period of two weeks in Shah Alam, our lecturers who applied for the course found themselves having to uproot from the usual routine of work and family life. Life throughout the course was indeed grueling. Mornings were filled with lectures, afternoons group projects and many spent sleepless nights pouring over their individual assignment.